Hybrids of acylated homoserine lactone and nitric oxide donors as inhibitors of quorum sensing and virulence factors in Pseudomonas aeruginosa1. Issue 38 (14th October 2015) - Kutty, Samuel K.; Barraud, Nicolas; Ho, Kitty K. K.; Iskander, George M.; Griffith, Renate; Rice, Scott A.; Bhadbhade, Mohan; Willcox, Mark D. P.; Black, David StC; Kumar, Naresh
<x xml:space="preserve">Abstract</x> This paper discusses conversion of agonist acylated homoserine lactones (AHL) to antagonist AHLs with dual properties of quorum sensing inhibition and nitric oxide release.